The antineoplastic drugs cyclophosphamide and cisplatin in the aquatic environment - review - Queirós, Vanessa (2021)
Cyclophosphamide (CP) and Cisplatin (CDDP) are antineoplastic drugs widely used in the treatment of neoplastic diseases that have been detected in the aquatic environment. This review summarizes the current knowledge on the presence in the aquatic environment of these two drugs and their effects on freshwater and marine invertebrates, which includes good model species in ecotoxicology and risk assessment programs. The consumption levels, occurrence in freshwater and marine ecosystems, and the impacts exerted on aquatic organisms, even at low concentrations, justifies this review and the selection of these two drugs. Both pharmaceuticals were detected in different aquatic environments, with concentrations ranging from ng L-1 up to 687.0 μg L-1 (CP) and 250 μg L-1 (CDDP). The available studies showed that CP and CDDP induce individual and sub-individual impacts on aquatic invertebrate species. The most common effects reported were changes in the reproductive function, oxidative stress, genotoxicity, cytotoxicity and neurotoxicity. The literature used in this review supports the need to increase monitoring studies concerning the occurrence of antineoplastic drugs in the aquatic environment since negative effects have been reported even at trace concentrations (ng L-1). Furthermore, marine ecosystems should be considered as a priority since less is known on the occurrence and effects of antineoplastic drugs in this environment comparing to freshwater ecosystems.